Die ökonomische Politik Deutschlands gegenüber dem polnischen Königreich im ersten Weltkrieg [Germany’s economic policy towards the Polish Kingdom in World War I] - Łuczak, Czesław (Studia Historiae Oeconomicae, 2001)
The military victories won by the German Reich on the Eastern Front in the early stages of World War I and the resulting occupation of part of the Kingdom of Poland contributed to the development of existing and new plans for the Germanization of the areas bordering Germany's eastern border. These plans primarily envisaged the creation of a border region in the western part of the Kingdom of Poland populated by Germans. It was intended to separate Poles in the Prussian occupation zone from their compatriots living in the Kingdom of Poland. The territorial area of ​​this region was defined differently in individual plans, but most of them envisaged it being bordered by the Warta, Narew, Biebrza and Memel rivers.